2019
DOI: 10.1021/acsenergylett.9b00403
|View full text |Cite
|
Sign up to set email alerts
|

Intralayer A-Site Compositional Engineering of Ruddlesden–Popper Perovskites for Thermostable and Efficient Solar Cells

Abstract: Layered Ruddlesden–Popper (RP) perovskites have good moisture- and photostability. However, thermal stability of the RP perovskites is still a challenge. In this work, through a joint theoretical and experimental study, we report an intralayer A-site compositional engineering strategy to enhance the thermal stability of the RP perovskite solar cells. The triple-A-site-cation BA2(MA0.76FA0.19Cs0.05)3Pb4I13 (labeled as T-RP) cells retain 80% of the initial efficiency after being stressed at a constant temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 47 publications
0
48
0
Order By: Relevance
“…Inspired by cation engineering in 3D perovskite, through the double doping or triple doping of A-site ions, the decomposition energy of perovskite can be improved, thereby improving stability (as shown in Figure 6a). [115][116][117] The A-site ion doping can also induce the preferred orientation of 2D perovskite during the fabrication process. However, it is a key point to understand the relationship between the crystal microstructure and crystallization kinetics, which is related to the carrier transport of 2D perovskite materials.…”
Section: Ion Composition Of Precursormentioning
confidence: 99%
“…Inspired by cation engineering in 3D perovskite, through the double doping or triple doping of A-site ions, the decomposition energy of perovskite can be improved, thereby improving stability (as shown in Figure 6a). [115][116][117] The A-site ion doping can also induce the preferred orientation of 2D perovskite during the fabrication process. However, it is a key point to understand the relationship between the crystal microstructure and crystallization kinetics, which is related to the carrier transport of 2D perovskite materials.…”
Section: Ion Composition Of Precursormentioning
confidence: 99%
“…As shown in Figure S22 (Supporting Information), the absorption spectra of (BEA) 0.5 Cs 0.15 (FA 0.83 MA 0.17 ) 2.85 Pb 3 (I 0.83 Br 0.17 ) 10 film is dominated by excitonic peaks, indicating BEA based mixed cation perovskite is also a series of quasi‐2D/3D mixture. Furthermore, XRD patterns and SEM images (Figure S23, Supporting Information) of BEA + mixed cations perovskites films demonstrate that the triple‐A‐site cation with BEA ligand (BEA) 0.5 Cs 0.15 (FA 0.83 MA 0.17 ) 2.85 Pb 3 (I 0.83 Br 0.17 ) 10 perovskite is B ‐ACI structure, which derives from the structure of (BEA) 0.5 MA 3 Pb 3 I 10 . Figure c shows the J – V characteristics of the mixed cation devices.…”
Section: Carrier Characteristics Of (Bea)05ma3pb3i10 and (Ba)2ma2pb3mentioning
confidence: 99%
“…22,[29][30][31] From the commercialization of perovskite-based solar cell technology point of view, there is an urgent need to improve the stability of the perovskites in the near future. In literature, there are very few 2D perovskite materials reported that are stable under humid conditions, 29,32,33 thermal stress [34][35][36] and continuous illumination to UV light. 29 The quest to develop a stable perovskite material that can outperform under ambient conditions has motivated us to investigate the long carbon chain (C 14 , C 16 and C 18 ) organic cations in 2D perovskite.…”
Section: Introductionmentioning
confidence: 99%